The Profile of Professional, Pedagogical, Social, and Personal Competence of Elementary School Teacher Education Graduates - Andayani, Andayani; Handayani, Monika; Hanafi, Hanafi; Mardiana, Ade; Prabowo, Suryo; Saputra, Alfin Herman (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to provide an overview of 4 (four) competencies that must be possessed by teachers, namely Professional, Social Pedagogic, and Personality from graduates of the Open University (UT) S1 Study Program Elementary School Teacher Program (PGSD) from various regions in Indonesia. . The research method used in this research is descriptive evaluative. This research was conducted in 112 (one hundred and twelve) elementary schools (SD), both public and private. The total number of graduates who became respondents in this study was 182 (one hundred and eighty-two). Data was collected by distributing questionnaires to the principals of these schools. The results of this study indicate that 4 (four) competencies possessed by UT graduates generally fall into the good category. The four competencies that need to be paid more attention to are professional, especially those related to research/scientific works and as resource persons in educational activities. This is a recommendation for UT to prepare teachers for the competencies that need attention.